2020
DOI: 10.1186/s42397-020-00075-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes controlling fiber quality traits in upland cotton through integration of meta-QTL, significant SNP and transcriptomic data

Abstract: Background Meta-analysis of quantitative trait locus (QTL) is a computational technique to identify consensus QTL and refine QTL positions on the consensus map from multiple mapping studies. The combination of meta-QTL intervals, significant SNPs and transcriptome analysis has been widely used to identify candidate genes in various plants. Results In our study, 884 QTLs associated with cotton fiber quality traits from 12 studies were used for meta-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Large array of candidate genes were identified within the QTL reported in this study ( Supplementary Table 2 ), and they were compared and annotated with Xu et al (2020) , where meta-QTL analysis along with transcriptomic approach utilized for the identification of candidate genes related to fiber quality in upland cotton. Though there were genes specific to abiotic stress responses and productive traits, large numbers of genes identified in this study warrant the use of additional markers to fine map these QTL and identify precise genes involved for the target traits.…”
Section: Resultsmentioning
confidence: 99%
“…Large array of candidate genes were identified within the QTL reported in this study ( Supplementary Table 2 ), and they were compared and annotated with Xu et al (2020) , where meta-QTL analysis along with transcriptomic approach utilized for the identification of candidate genes related to fiber quality in upland cotton. Though there were genes specific to abiotic stress responses and productive traits, large numbers of genes identified in this study warrant the use of additional markers to fine map these QTL and identify precise genes involved for the target traits.…”
Section: Resultsmentioning
confidence: 99%
“…In our present study, we analyzed the chromosome location of MIR396 gene family and found eight genes were colocalized with seven meta‐QTLs related to fiber quality (one meta‐QTLs for FS, two meta‐QTLs for MIC, and four meta‐QTLs for FL) (Figure 2A). Among which, GhmiR396b_D13 was colocalized with the meta‐QTLs for FL and expressed differently between Long and Short fibers (Figure 2B) (Ali et al, 2018; Jia et al, 2018; Ma et al, 2018; Xu et al, 2020). This result suggests that GhmiR396b_D13 has a critical role in the development of FL.…”
Section: Discussionmentioning
confidence: 99%
“…To identify new QTLs in this study, QTLs from our results were compared with previously reported QTLs. Previous MIC QTLs were retrieved from CottonGen ( Yu et al, 2014 ) and Cotton QTLdb Release 2.3 (January 24, 2018, see text footnote 1) ( Said J. et al, 2015 ) and from recent reports by Majeed et al (2019) and Xu et al (2020) . In addition, MIC QTL data from previous GWAS reports were also obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Through a meta-analysis of numerous QTL reports, Said J. et al (2015) compiled a total of 395 QTLs related to MIC in a QTL database for cotton. 1 Xu et al (2020) recently performed a meta-analysis and identified a total of 15 meta-QTLs for MIC. These studies provide references for locations of QTLs for MIC.…”
Section: Introductionmentioning
confidence: 99%